2010
DOI: 10.2754/avb201079030443
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Tularemia Disease Progress by the Bisquaternary Pyridinium Oxime HI-6

Abstract: Cholinesterase reactivator HI-6 is a drug commonly used to treat individuals exposed to nerve agents. Recent experiments proved HI-6 impact on parasympathetic response and impact on the nervus vagus associated cholinergic anti-inflammatory pathway is hypothesized here. The modulation effect of HI-6 was studied on BALB/c mice infected with Francisella tularensis, the bacteria causing tularemia. Cultivation test in vitro confirmed weak bacteriostatic effects of HI-6. Results in experiments revealed intriguing ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Recently, HI-6 was recognized as an immunomodulatory compound, significantly modifying the progression of infection and disease represented by tularemia (Pohanka et al, 2010). Vrdoljak et al (2009) found that HI-6 relieves to suppress the side effects of topoisomerase 1 inhibitor irinotecan, which is approved for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HI-6 was recognized as an immunomodulatory compound, significantly modifying the progression of infection and disease represented by tularemia (Pohanka et al, 2010). Vrdoljak et al (2009) found that HI-6 relieves to suppress the side effects of topoisomerase 1 inhibitor irinotecan, which is approved for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that these compounds can bind like acetylcholine due to the quarternary ammonium atom and interact with AChE and with AChR [ 86 , 87 ]. Biological effects HI-6 (asoxime; Figure 3 ) are considered to be associated with α7 nAChR; unfortunately the plausible proof is still missing [ 88 , 89 ]. The antagonists of α7 nAChR are summarized in Table 1 .…”
Section: Antagonists Of α7 Nachrmentioning
confidence: 99%